Preparation method of biodegradable and bacteriostatic bamboo fiber-based paper straw

By bleaching bamboo fibers into paper and pretreatment, and combining the treatment of stearic acid and phytic acid, bamboo fiber-based paper straws were prepared, which solved the problems of complex structure and high preparation cost of existing straws, and achieved multiple properties of biodegradability, antibacterial and hydrophobicity, and was suitable for the food field.

CN119593255AActive Publication Date: 2025-03-11NORTHEAST FORESTRY UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510009391.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-11
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The existing bamboo fiber paper straws have complex structures and high production costs, which are difficult to meet the market's demand for low-cost and easy-to-prepared biodegradable straws.

Method used

Paper is made by bleaching bamboo fibers and pretreated with citric acid and chitosan quaternary ammonium solution to increase the crosslinking effect between the fibers. The pipette is then prepared by curling and soaked in a mixed solution of stearic acid and phytic acid, giving the pipette excellent hydrophobic properties and antibacterial properties.

Benefits of technology

The biodegradability, antibacteriality and hydrophobicity of bamboo fiber-based paper straws are realized. The straw is completely degraded within 40 days, and has good antibacterial effects and wide application. At the same time, the preparation method is green, low-carbon and pollution-free throughout the whole process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593255A_ABST
    Figure CN119593255A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a biodegradable and bacteriostatic bamboo fiber-based paper straw, and relates to a preparation method of a paper straw. The technical problems that an existing bamboo fiber paper straw is complex in structure and high in manufacturing cost are solved. The method comprises the following steps: firstly, soaking made bamboo fiber-based paper with a citric acid solution, then soaking the bamboo fiber-based paper with a chitosan quaternary ammonium salt solution, rolling a pipe, and drying; soaking the bamboo fiber base paper with an ethanol solution of stearic acid and phytic acid, and drying the bamboo fiber base paper to obtain the biodegradable and bacteriostatic bamboo fiber base paper straw. The contact angle of the straw can still reach 90-120 degrees after the straw is in contact with water for 30 minutes, the antibacterial rates on escherichia coli and staphylococcus aureus respectively reach 100% and 99.63%, the straw is completely degraded under the soil burying condition for 40 days, and the straw is suitable for various drinks such as tea, coffee, milk and cola and can be used in the field of food.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a paper straw. Background Art

[0002] Plastic products have been widely used in daily life due to their advantages such as light weight, low cost, durability and easy production. However, microplastics produced during the degradation and weathering of plastic products will spread into the food chain and are difficult to degrade, which has a negative impact on the environment and human health. In particular, polypropylene plastic straws (PP) are disposable products. Due to their light weight, small size and difficulty in recycling, replacing plastic straws with biomass-based straws has become an inevitable trend in the development of the industry.

[0003] Cellulose is the most abundant green resource on earth. It is renewable, biodegradable, and low-cost, making it a potential material for making straws. Bamboo is also one of the most important non-wood forest resources. It is widely distributed and comes in many varieties. The pulping and papermaking process using bamboo is also quite mature. For example, a Chinese patent with application number CN202221658830.X discloses a naturally degradable paper straw, the interior of which is provided with a detachable structure, and the interior of the straw body is provided with a durable structure, the durable structure including kraft paper, which is arranged inside the straw body, and bamboo fiber is arranged on one side of the kraft paper, and a polylactic acid film is arranged on the other side of the kraft paper. The paper straw has a complex structure and a high preparation cost. Summary of the invention

[0004] The present invention aims to solve the technical problems of the existing bamboo fiber paper straws, which have complex structures and high preparation costs, and to provide a method for preparing biodegradable and antibacterial bamboo fiber-based paper straws. The paper straws have excellent hydrophobic and antibacterial properties.

[0005] The method for preparing the biodegradable and antibacterial bamboo fiber-based paper straw of the present invention is carried out according to the following steps:

[0006] 1. Making bamboo fiber-based paper;

[0007] 2. Cut the bamboo fiber-based paper into rectangles, soak the paper with a citric acid solution having a mass percentage concentration of 10% to 15%, and then soak the paper with a chitosan quaternary ammonium salt solution having a concentration of 10 to 15 g / L; then roll the moistened rectangular wet paper onto a polytetrafluoroethylene (PTFE) rod, press the edges together, dry at room temperature, and separate from the PTFE rod to obtain a CA / CQAS / BBF straw;

[0008] 3. Using anhydrous ethanol as solvent, add stearic acid and phytic acid to anhydrous ethanol at a mass percentage concentration of 10% to 22% of stearic acid and 5% to 20% of phytic acid, mix well and heat to 65 to 70°C under stirring until the solution becomes clear to obtain a mixed solution; then soak the CA / CQAS / BBF straws obtained in step 2 in the mixed solution for 10 to 20 minutes, take out and dry naturally at room temperature to obtain biodegradable, antibacterial bamboo fiber-based paper straws, recorded as SA / PA / BBF straws.

[0009] Furthermore, the method for making bamboo fiber-based paper in step 1 is carried out according to the following steps:

[0010] (1) firstly adding the bleached bamboo pulp board into water and soaking it for 10 to 12 hours, and then beating it to make the pulp concentration be 1% to 1.5%; then using a pulping machine to adjust the final beating degree to 30 to 35°SR, and after the beating is completed, dehydrating it to obtain a pulp block;

[0011] (2) According to the quantitative 80 ~ 85g / m 2 The pulp block is added into water, and is disintegrated by a fiber standard disintegrator for 10,000 revolutions. The pulp is filtered through a paper sheet former with a filter screen of 250 to 300 meshes to obtain a wet paper web. Both sides of the wet paper web are removed with clean absorbent paper, and the wet paper web is first placed in a pneumatic paper sheet press for pressing for 5 to 10 minutes, and then dried on both sides in a flat paper sample dryer at a temperature of 100 to 105° C. for 5 to 10 minutes to obtain a bamboo fiber-based paper.

[0012] Furthermore, the average mass of the rectangular bamboo fiber base paper described in step 2 is m=0.2-0.3g.

[0013] Furthermore, the rectangular bamboo fiber base paper described in step 2 has a size of (3-4) cm×(10-12) cm.

[0014] The present invention uses bleached bamboo fiber as raw material, prepares paper through a papermaking process, then increases the cross-linking effect between fibers through pretreatment with citric acid (CA) and chitosan quaternary ammonium salt (CQAS) solution, and then obtains paper straws through curling, and then soaks the straws in a mixed solution of stearic acid (SA) and phytic acid (PA) to give the straws excellent hydrophobic and antibacterial properties. The contact angle of the biodegradable and antibacterial bamboo fiber-based paper straw of the present invention can still reach 90 to 120° after contacting with water for 30 minutes. The hydrophobic effect of the straw is verified by water absorption rate and contact angle. At the same time, the antibacterial rate of Escherichia coli reaches 100%, and the antibacterial rate of Staphylococcus aureus reaches 99.63%, and has good antibacterial effect. The straw achieves 100% complete degradation under 40-day soil burial conditions, and is suitable for various beverages such as tea, coffee, milk, cola, etc., showing a wide range of applicability and good stability in room temperature and 0°C aqueous solution. At the same time, the preparation method is a green, low-carbon and pollution-free method in the whole process, and a safe and green antibacterial straw is obtained. The straw of the invention is a bamboo fiber-based paper straw with good water stability, biodegradability and antibacterial properties, and can be used in the food field. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a comparison diagram of the maximum water contact angles of BBF, CA / CQAS / BBF straws and SA / PA / BBF straws in Example 1;

[0016] Figure 2 Surface and cross-sectional SEM images of BBF, CA / CQAS / BBF straws and SA / PA / BBF straws in Example 1;

[0017] Figure 3 Element distribution diagram of SA / PA / BBF straw prepared in Example 1;

[0018] Figure 4 FTIR spectra of BBF, CA / CQAS / BBF straws, SA / PA / BBF straws prepared in Example 1, CA / CQAS / SA / BBF straws prepared in the comparative example, and SA;

[0019] Figure 5 XRD spectra of BBF, CA / CQAS / BBF straws, SA / PA / BBF straws prepared in Example 1, CA / CQAS / SA / BBF straws prepared in the comparative example, and SA;

[0020] Figure 6 TGA curves and DTG curves of BBF, CA / CQAS / BBF straws, SA / PA / BBF straws prepared in Example 1, CA / CQAS / SA / BBF straws prepared in Comparative Example 1, and SA;

[0021] Figure 7 This is a graph showing the antibacterial evaluation of BBF, CA / CQAS / BBF straws, and SA / PA / BBF straws prepared in Example 1 on Escherichia coli and Staphylococcus aureus;

[0022] Figure 8 This is a comparison chart of the dry bending strength of the BBF, CA / CQAS / BBF straws, and SA / PA / BBF straws prepared in Example 1;

[0023] Fig. 9 This is a diagram of the wet bending strength of the SA / PA / BBF straw prepared in Example 1;

[0024] Fig.10 Degradation test diagram of SA / PA / BBF straws, PP straws, PLA straws and commercial paper straws prepared in Example 1;

[0025] Fig.11 The water stability graphs of BBF, CA / CQAS / BBF straws, and SA / PA / BBF straws prepared in Example 1 at 25°C;

[0026] Fig.12 This is a comparison chart of the applicability of BBF, CA / CQAS / BBF straws, and SA / PA / BBF straws prepared in Example 1 in four beverages;

[0027] Fig.13 This is a comparison chart of the applicability of BBF, CA / CQAS / BBF straws, and SA / PA / BBF straws prepared in Example 1;

[0028] Fig.14 This is a comparison chart of the water stability of BBF, CA / CQAS / BBF straws, and SA / PA / BBF straws prepared in Example 1 at 0°C;

[0029] Fig.15 Performance radar chart of SA / PA / BBF straws, commercial paper straws and PLA straws prepared in Example 1;

[0030] Fig.16 These are contact angle photographs of the biodegradable, antibacterial bamboo fiber-based paper straws prepared in Examples 2 to 5. DETAILED DESCRIPTION

[0031] The beneficial effects of the present invention are verified by the following examples.

[0032] Example 1: The preparation method of the biodegradable and antibacterial bamboo fiber-based paper straw of this example is carried out according to the following steps:

[0033] 1. To make bamboo fiber-based paper, the specific method is as follows:

[0034] (1) First, bleached bamboo pulp is added into water and soaked for 12 hours, and then pulped to make the pulp concentration at 1.5%; then, a Valley pulper is used to adjust the final beating degree to 30°SR, and after the pulping is completed, dehydration is performed to obtain pulp blocks;

[0035] (2) According to the quantitative 80g / m 2 The pulp block was added into water, and was disintegrated by GBJ-A fiber standard disintegrator for 10,000 revolutions. The pulp was filtered through a paper sheet former with a filter mesh of 250 meshes to obtain a wet paper web. Both sides of the wet paper web were removed with clean absorbent paper, and the wet paper web was first placed in a PL8-B pneumatic paper sheet press for 5 minutes, and then dried on both sides in a PL7-C flat paper sample dryer at a temperature of 105°C for 5 minutes each. The bamboo fiber base paper was peeled off from the absorbent paper, which was recorded as BBF.

[0036] 2. Cut bamboo fiber-based paper into rectangles of 3 cm × 10 cm, with an average mass of m = 0.25 g for each rectangular paper sheet. First, soak the paper sheet with a citric acid solution having a mass percentage concentration of 10%, and then soak the paper sheet with a chitosan quaternary ammonium salt solution having a concentration of 10 g / L; then roll the moistened rectangular wet paper sheet onto a polytetrafluoroethylene (PTFE) rod, press the edges together tightly, dry at room temperature, and separate from the PTFE rod to obtain a CA / CQAS / BBF straw;

[0037] 3. Using anhydrous ethanol as solvent, add stearic acid and phytic acid to anhydrous ethanol at a mass percentage concentration of 13% and 14% respectively, mix well and heat to 70°C under stirring until the solution becomes clear to obtain a mixed solution; then soak the CA / CQAS / BBF straws obtained in step 2 in the mixed solution for 14 minutes, take out and dry naturally at room temperature to obtain biodegradable, antibacterial bamboo fiber-based paper straws, recorded as SA / PA / BBF straws.

[0038] Comparative Example 1: This comparative example is different from Example 1 in that step 3 is replaced by the following operation:

[0039] 3. Prepare a stearic acid solution with a mass percentage concentration of 20%; then soak the CA / CQAS / BBF tube obtained in step 2 in the stearic acid solution for 14 minutes, take it out and dry it naturally at room temperature to obtain a bamboo fiber-based paper straw, which is recorded as CA / CQAS / SA / BBF straw. The other steps and parameters are the same as those in Example 1.

[0040] The BBF obtained in step 1, the CA / CQAS / BBF straw obtained in step 2, and the SA / PA / BBF straw obtained in step 3 of this embodiment were tested for contact angle. The contact angles obtained are as follows: Figure 1 As shown, from Figure 1It can be seen that the maximum water contact angles of BBF and CA / CQAS / BBF tubes are 26° and 37°, respectively, while the initial contact angle of the SA / PA / BBF straws obtained in step three is as high as 134.4°, and the WAC is still 119° after 30 minutes. Compared with CA / CQAS / SA / BBF straws, the hydrophobic stability of straw paper is improved overall by the treatment with phytic acid. It is confirmed that the mixed treatment of phytic acid and stearic acid improves the hydrophobic properties through the mutual cross-linking of anions and cations with the cations in CQAS. At the same time, SA enhances the surface roughness of the straw, and its crystalline state increases the repulsion of water molecules, playing a vital role in the hydrophobic effect.

[0041] Figure 2 The SEM images of the surface and cross section of the BBF obtained in step 1, the CA / CQAS / BBF straw obtained in step 2, and the SA / PA / BBF straw obtained in step 3 are shown, respectively. a and d are SEM images of the surface of BBF, b and e are SEM images of the surface of CA / CQAS / BBF, c and f are SEM images of the surface of SA / PA / BBF, g is SEM image of the cross section of BBF, h is SEM image of the cross section of CA / CQAS / BBF, and i is SEM image of the cross section of SA / PA / BBF. From a, d, and g, it can be seen that the bleached bamboo fibers (BBF) are interconnected, and there are a large number of pores between the fibers. Water molecules can easily enter the internal structure, causing the straw paper to be super hydrophilic at this time. From b, e, and h, it can be seen that after the fibers are treated with CA and CQAS, the anions in CA and the cations in CQAS interact with each other, making the fibers more closely cross-linked and reducing the pores. From c, f, and i, it can be seen that the fiber surface and cross-section of the BBF modified by the mixture of SA and PA show a dense structural state. The anions in SA and PA enhance the density of the fiber surface by combining with the cations in CQAS. At the same time, the stearic acid crystals enhance the surface roughness of the fiber by attaching to the surface of the fiber, which makes it possible for the SA / PA / BBF straw to achieve high water resistance and hydrophobicity.

[0042] Figure 3 The element distribution diagram of SA / PA / BBF obtained in step 3 of Example 1 is shown in FIG. Figure 3 It can be seen that the C, N, O, and P elements are evenly distributed in the SA / PA / BBF straws, with contents of 36%, 6%, 10%, and 7%, respectively, which confirms that phytic acid has been successfully introduced into the surface of the straw paper.

[0043] Figure 4 FTIR spectra of BBF, CA / CQAS / BBF straws, SA / PA / BBF straws, CA / CQAS / SA / BBF straws prepared in Comparative Example 1, and SA. Figure 4 It can be seen that for the BBF straw, at 3321 cm -1 and 2901cm -1 The peaks at 1326cm belong to the vibration of OH and CH. -1 and 1023cm -1 The peaks at 1724 cm and 1764 cm are caused by the bending vibration of OH and the stretching vibration of CO, respectively. Some changes were observed after CA / CQAS treatment, and a new peak appeared at 1724 cm -1 , which belongs to the stretching vibration of C=O. There are multiple CA molecules on the surface of paper straws that form a dense cross-linked network structure with CQAS molecules. Some changes were observed after treatment with SA and PA. New peaks appeared at 1702cm -1 、1471cm -1 and 1380-1150cm -1 At 945cm, the stretching vibration of C=O and the bending vibration of methyl and methylene of SA are found. The results show that SA and PA are successfully combined with bamboo fiber. -1 The strong band at shows the C-type polymorphic form of SA, which is consistent with the wide-angle X-ray diffraction (WAXD) results.

[0044] Figure 5 The XRD spectra of the SA, BBF, CA / CQAS / BBF straws, SA / PA / BBF straws and CA / CQAS / SA / BBF straws prepared in Example 1 are shown in Table 1. Figure 5 It can be seen that crystal peaks with different spacing lengths can be seen in stearic acid crystals. The "long spacing" of stearic acid appears (7.2°), (11.7°) and (15.5°) three different diffraction peaks, indicating the thickness and orderly arrangement of stearic acid molecules. (21.6°) and The "short spacing" appears at the diffraction angle of (23.9°), indicating the lateral stacking order of hydrocarbon chains. The BBF straw, CA / CQAS / BBF straw, and CA / CQAS / SA / BBF straw show characteristic peaks of cellulose I at 16.5° and 22.6°. For the CA / CQAS / SA / BBF straw, the peaks at 7.2°, 11.7°, 21.6°, and 23.9° represent the intercrystalline spacing of SA, indicating that SA exists on the surface in a crystalline state. These values ​​are in good agreement with monoclinic C-stearic acid.

[0045] Figure 6The TGA curves and DTG curves of the BBF, CA / CQAS / BBF tubes, SA / PA / BBF straws in Example 1 and the CA / CQAS / SA / BBF straws prepared in Comparative Example 1 are shown in Figure 1, where a is the TGA curve and b is the DTG curve. The thermal stability of the straw is related to whether the straw can be put into production and use normally. Figure 6 It can be seen that before the temperature rises to 160°C, CA / CQAS / BBF straws, CA / CQAS / SA / BBF straws and SA / PA / BBF straws lose weight slowly. However, before the temperature rises to 280°C, BBF loses weight slowly, which is attributed to the evaporation of water on the surface of the straw paper. As the temperature continues to rise, the rate of weight loss of the sample gradually accelerates. SA begins to decompose at around 207°C, CA decomposes at around 176°C, CQAS decomposes at around 331°C, PA decomposes at around 260°C, and the fibers of uncoated paper decompose at around 348°C. When the temperature reaches 379°C, the mass of the sample gradually stabilizes. Compared with uncoated paper, the residual mass of the modified paper increases and the thermal weight loss rate decreases, which may be related to the changes in fiber size and crystal structure during the modification process. All straws have good thermal stability at less than 100°C, indicating that the straws can be used in normal life.

[0046] The antibacterial properties of the BBF straws, SA / PA / BBF straws, and CA / CQAS / SA / BBF straws of Comparative Example 1 prepared by the classical colony counting method are compared as shown in the figure below. Figure 7 As shown, from Figure 7 It can be seen that the CA / CQAS / SA / BBF straws have poor antibacterial properties against Escherichia coli and Staphylococcus aureus, which are 21.94% and 67.65% respectively, while the SA / PA / BBF straws treated with phytic acid can achieve an antibacterial rate of 100% against Escherichia coli and 99.63% against Staphylococcus aureus. This is because PA contains 6 active phosphate groups, which chelate with divalent cations in lipopolysaccharide, reduce the pH value of the environment, and cause cell wall damage. The integrity of the bacterial cell wall and cell membrane is destroyed, the permeability increases, and the bacterial cytoplasm leaks out, resulting in an increase in alkaline phosphatase content and conductivity. PA can not only make the bacterial surface rough, but also cause ruptures, collapses and holes on the cell surface, thereby causing the leakage of cell protoplasm.

[0047] The dry bending strength comparison of the BBF straws, CA / CQAS / BBF straws and SA / PA / BBF straws prepared in Example 1 is shown in FIG. Figure 8 As shown by Figure 8 It can be seen that with the change of treatment methods, the three types of straws are completely bent under loads of 110g, 130g and 180g in air, respectively. It can be seen that the bending strength of the straws is enhanced after treatment with CA, CQAS and SA, PA.

[0048] The comparison of the load-bearing capacity of the SA / PA / BBF straws prepared in Example 1 in water is shown in the figure below: Fig. 9 As shown in the figure, BBF straws and CA / CQAS / BBF straws have poor bearing capacity in water. They soften immediately after being immersed in water and cannot bear any weight. Fig. 9 It can be seen that the SA / PA / BBF straw can carry a weight of 50 g for 2 min when fully immersed in water, because the anions in SA and PA combine with the cations in CQAS to improve the compactness of the fiber, and SA is attached to the fiber surface, thereby improving the water stability. At the same time, as shown in Table 1, the mechanical strength (TS and EB) of the SA / PA / BBF straw still needs to be improved.

[0049] Table 1 Comparison of mechanical properties of different straws

[0050]

[0051] PP straws, PLA straws, commercial paper straws and the SA / PA / BBF straws prepared in Example 1 were subjected to degradation tests. PP straws, PLA straws, commercial paper straws and the SA / PA / BBF straws prepared in Example 1 were buried in the same soil environment to observe the morphological changes of the different straws within 40 days. Fig.10 As shown, from Fig.10 It can be seen that SA / PA / BBF straws were completely degraded within 40 days, and their degradation rate was better than that of commercial paper straws. In contrast, PP and PLA straws did not degrade significantly during the same period, highlighting their poor biodegradability. SA / PA / BBF straws are expected to replace plastic straws to partially solve the white pollution problem due to their excellent biodegradability.

[0052] The hydrophilicity and hydrophobicity comparison of the BBF straws, CA / CQAS / BBF straws and SA / PA / BBF straws prepared in Example 1 at room temperature is shown in the figure below. Fig.11 As shown. By immersing each straw in a bright blue solution, the capillary action was observed. The results showed that the BBF straw and the CA / CQAS / BBF straw were superhydrophilic. The bright blue solution reached the top of the straw within 2 minutes and 3 minutes, respectively, causing the straw to swell, soften, and lose fibers. However, the SA / PA / BBF straw was stable in shape within 4 hours without any signs of delamination or edge cracking, and it could still maintain a straight shape after being taken out of the solution.

[0053] The BBF straws, CA / CQAS / BBF straws and SA / PA / BBF straws prepared in Example 1 were immersed in tea, coffee, cola and milk, respectively, to simulate the usage scenarios. Fig.12As shown. BBF straws only lasted 2 minutes, 4 minutes, 1 minute, and 3 minutes in tea, coffee, cola, and milk, respectively. CA / CQAS / BBF straws only lasted 3 minutes, 5 minutes, 3 minutes, and 7 minutes in tea, coffee, cola, and milk, respectively. The overall maintenance time showed a trend of extension, but it still could not meet the needs of practical applications. In contrast, SA / PA / BBF straws maintained their shape stability after being immersed in all beverages for 2 hours, without expansion or bending, etc., showing their superior stability and durability. Fig.13 shown.

[0054] The water stability of the BBF straws, CA / CQAS / BBF straws and SA / PA / BBF straws prepared in Example 1 at 0°C was tested. The BBF straws, CA / CQAS / BBF straws and SA / PA / BBF straws were immersed in 0°C water to evaluate their applicability. Fig.14 As shown. Fig.14 It can be seen that within 2 and 3 minutes, the BBF straw and CA / CQAS / BBF straw were fully soaked due to capillary action, and the water continued to extend to the top of the straw, and softened and collapsed, respectively. In contrast, the SA / PA / BBF straw could still maintain its original shape even after 2 hours, without any signs of delamination or cracking.

[0055] The performance radar chart of SA / PA / BBF straws, commercial paper straws and PLA straws prepared in Example 1 is as follows: Fig.15 As shown, from Fig.15 It can be seen that SA / PA / BBF straws were comprehensively compared with two commonly used biodegradable straws (PLA and commercial paper straws) in terms of manufacturing and performance parameters such as cost, biodegradability, wax coverage, taste, hydrophobicity, and mass productivity. The cost of SA / PA / BBF straws is approximately 5 times and 10 times lower than that of PLA straws and paper straws, respectively. In addition, PLA straws require specific conditions to achieve complete degradation. The surface of commercial paper straws solves the problem of water stability by covering it with multiple layers of waterproof wax, which not only increases the cost but also limits the speed of large-scale production. In contrast, SA / PA / BBF straws effectively solve the main shortcomings of PLA and paper straws and have excellent antibacterial properties against Escherichia coli and Staphylococcus aureus, and are expected to become a superior alternative to plastic straws.

[0056] Example 2: This example is different from Example 1 in that the concentration of the stearic acid solution in step 3 is 10%, and the rest is the same as Example 1. The obtained biodegradable and antibacterial bamboo fiber-based paper straws are denoted as SA10 / PA13 / BBF straws.

[0057] Example 3: This example is different from Example 1 in that the concentration of the stearic acid solution in step 3 is 18%, and the rest is the same as Example 1. The obtained biodegradable and antibacterial bamboo fiber-based paper straws are denoted as SA18 / PA13 / BBF straws.

[0058] Example 4: This example is different from Example 1 in that the concentration of the phytic acid solution in step 3 is 10%, and the rest is the same as Example 1. The obtained biodegradable and antibacterial bamboo fiber-based paper straws are denoted as SA14 / PA10 / BBF straws.

[0059] Example 5: This example is different from Example 1 in that the concentration of the phytic acid solution in step 3 is 20%, and the rest is the same as Example 1. The obtained biodegradable and antibacterial bamboo fiber-based paper straws are denoted as SA14 / PA20 / BBF straws.

[0060] The contact angle photos of the biodegradable, antibacterial bamboo fiber-based paper straws prepared in Examples 2 to 5 are shown in FIG. Fig.16 The specific data are shown in Table 2. Fig.16 As shown in Table 2, the addition of PA improved the hydrophobic stability of the straw as a whole. After 30 minutes, the contact angle of the straw paper was still maintained above 90°, showing good stability.

[0061] Table 2 Contact angles of SA / PA / BBF straws prepared in Examples 2 to 5

[0062] sample Straw name Contact angle after 30 minutes of contact with water Example 2 SA10 / PA13 / BBF 95.9° Example 3 SA18 / PA13 / BBF 91° Example 4 SA14 / PA10 / BBF 95.2° Example 5 SA14 / PA20 / BBF 95.6°

[0063] The present invention utilizes bleached bamboo pulp to make paper to obtain formed paper, and pre-treats the straw paper through the ionic bond interaction between citric acid and chitosan quaternary ammonium salt. Stearic acid (SA) is a saturated fatty acid extracted from animals and plants, which can be found in almost all oils and fats. It is a fatty acid with a very wide source. Its unique 18-carbon structure gives stearic acid the potential for hydrophobicity. The present invention achieves hydrophobic modification of straws by adding stearic acid. Phytic acid (PA) is a non-toxic, renewable, low-cost natural compound extracted from plants such as soybeans and corn. Due to its special structure with six phosphate groups, it has excellent antibacterial properties. The present invention gives the straw good antibacterial properties by adding phytic acid. The straw also exhibits excellent biodegradability and wide applicability.

Claims

1. A method for preparing a biodegradable, antibacterial bamboo fiber-based paper straw, characterized in that The method proceeds as follows:

1. Making bamboo fiber-based paper; 2. Cut the bamboo fiber-based paper into a rectangle, first soak the paper with a citric acid solution with a mass percentage concentration of 10% to 15%, and then soak the paper with a chitosan quaternary ammonium salt solution with a concentration of 10 to 15 g / L; then roll the moistened rectangular wet paper onto a polytetrafluoroethylene rod, press the edges together, dry at room temperature, and separate from the PTFE rod to obtain a CA / CQAS / BBF straw; 3. Using anhydrous ethanol as solvent, add stearic acid and phytic acid to anhydrous ethanol at a mass percentage concentration of 10% to 22% of stearic acid and 5% to 20% of phytic acid, mix well and heat to 65 to 70°C under stirring until the solution becomes clear to obtain a mixed solution; then soak the CA / CQAS / BBF straws obtained in step 2 in the mixed solution for 10 to 20 minutes, take out and dry naturally at room temperature to obtain biodegradable, antibacterial bamboo fiber-based paper straws, recorded as SA / PA / BBF straws.

2. The method for preparing a biodegradable, antibacterial bamboo fiber-based paper straw according to claim 1, characterized in that: The method for making bamboo fiber-based paper described in step 1 is carried out according to the following steps: (1) firstly adding the bleached bamboo pulp board into water and soaking it for 10 to 12 hours, and then beating it to make the pulp concentration be 1% to 1.5%; then using a pulping machine to adjust the final beating degree to 30 to 35°SR, and after the beating is completed, dehydrating it to obtain a pulp block; (2) According to the quantitative 80 ~ 85g / m 2 The pulp block is added into water, and is disintegrated by a fiber standard disintegrator for 10,000 revolutions. The pulp is filtered through a paper sheet former with a filter screen of 250 to 300 meshes to obtain a wet paper web. Both sides of the wet paper web are removed with clean absorbent paper, and the wet paper web is first placed in a pneumatic paper sheet press for pressing for 5 to 10 minutes, and then dried on both sides in a flat paper sample dryer at a temperature of 100 to 105° C. for 5 to 10 minutes to obtain a bamboo fiber-based paper.

3. The method for preparing a biodegradable, antibacterial bamboo fiber-based paper straw according to claim 1 or 2, characterized in that: The average mass of the rectangular bamboo fiber base paper described in step 2 is m=0.2-0.3g.

4. The method for preparing a biodegradable, antibacterial bamboo fiber-based paper straw according to claim 1 or 2, characterized in that: The rectangular bamboo fiber base paper described in step 2 has a size of (3-4) cm×(10-12) cm.

Citation Information

Patent Citations

  • Paper straw capable of being naturally degraded

    CN217743920U

  • Bamboo fiber barrier packaging paper as well as preparation method and application thereof

    CN117702526A

  • Method for preparing antibacterial texture

    KR1020030081228A